Relationship between gingival recession and tooth brushing habits - Hashem, Ahmed Shawkat; Patil, Santosh R; Issrani, Rakhi; Prabhu, Namdeo; Albalawi, Ahmed Saleh; Alam, Mohammad Khursheed (Bangladesh Journal of Medical Science, 2024)
Background: Gingival recession is a common periodontal condition that can lead to aesthetic and functional problems. Tooth brushing habits have been suggested to be associated with gingival recession, but the evidence on this relationship is limited. Aim: To investigate the relationship between gingival recession and tooth brushing habits in a sample of 100 patients. Methodology: A cross-sectional study was conducted on 100 patients aged between 20 and 60 years who presented to a dental clinic. Demographic data, tooth brushing habits, and gingival recession depth were recorded. Descriptive statistics were used to summarize the data, and logistic regression analysis was performed to investigate the association between tooth brushing habits and gingival recession. Results: The mean age of the participants was 40 years, and 52% of the participants were female. The mean gingival recession depth was 1.8 mm (SD=0.7). Majority of the participants brushed their teeth twice a day (65%), used manual tooth brushes (72%), used circular method for tooth brushing (54%), spent 2-3 minutes on tooth brushing (60%), and dental floss was the most commonly used additional oral hygiene aid (60%). The bivariate correlation analysis showed a statistically significant positive correlation between gingival recession and frequency of tooth brushing (r=0.28, p=0.01). Conclusion: The findings of this study suggest that tooth brushing habits are significantly associated with the development and progression of gingival recession. Thus, oral health professionals should educate their patients about the proper tooth brushing techniques and the use of additional oral hygiene aids to prevent the development of gingival recession. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 846-850